Two Unexpected Temperature-Induced Supermolecular Isomers from Multi-Topic Carboxylic Acid: Hydrogen Bonding Layer or Helix Tube - Chunyang Li; Chunhong Tan; Juan Zhou; Yan-Yong Lin; Xiao-Feng Wang (Molecules, 2021)
Under ambient conditions or 160 °C, two supramolecular isomers, namely [(H4PTTA)(H2O)2(DMF)] and [(H4PTTA)(H2O)3]··Guest (1-L and 1-H, H4PTTA = N-phenyl-N′-phenyl bicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxdiimide tetra-carboxylic acid, Guest = DMF and H2O), were obtained through the reaction of H4PTTA in a mixture of H2O and dimethylformamide. The single crystal structures reveal the temperature-dependent supramolecular isomerism derived from the torsion of semi-rigid of H4PTTA. The 1-L prepared at room temperature is a hydrogen bond based achiral layer, while the hydrothermal synthesized 1-H is isomer resulted in an H-bond-based chiral tubes-packed supramolecular framework.